2012
DOI: 10.1021/nn204886b
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Effects of CdSe Quantum Dot Size, Surface Charge, and Functionalization on Primary Human Lung Cells

Abstract: The growing potential of quantum dots (QDs) in applications as diverse as biomedicine and energy has provoked much dialogue about their conceivable impact on human health and the environment at large. Consequently, there has been an urgent need to understand their interaction with biological systems. Parameters such as size, composition, surface charge, and functionalization can be modified in ways to either enhance biocompatibility or reduce their deleterious effects. In the current study, we simultaneously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
136
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 63 publications
5
136
1
Order By: Relevance
“…[59] Specifically regarding QDs, studies have until now only reported that there is a lack of ROS induction by MPA-coated QDs. [34,35] Apart from ROS levels, we looked further into the impact of QD exposure on lysosomal health and autophagy. As a first step we evaluated the influence of QDs on the number and size of lysosomes.…”
Section: Mpa Coated Qdsmentioning
confidence: 99%
“…[59] Specifically regarding QDs, studies have until now only reported that there is a lack of ROS induction by MPA-coated QDs. [34,35] Apart from ROS levels, we looked further into the impact of QD exposure on lysosomal health and autophagy. As a first step we evaluated the influence of QDs on the number and size of lysosomes.…”
Section: Mpa Coated Qdsmentioning
confidence: 99%
“…Nanotechnologies open new horizons for application of new materials in biomedicine [1][2][3]. The current strategy for the development of advanced methods of tumor treatment focuses on targeted drug delivery to tumor cells [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Selenium, although is an essential nutrient for humans due it importance for many cellular processes also pose toxic potential [7] mainly above homeostatic requirements [8]. In vitro toxicity of QDs has been widely reported [9][10][11][12] including DNA damage [13].…”
Section: Introductionmentioning
confidence: 99%